Retrospective analysis of clinical manifestation in patients with primary cutaneous lymphomas - Lesiak, Aleksandra; Sobolewska, Dorota; Sysa-Jędrzejowska, Anna; Narbutt, Joanna (Dermatology Review/Przegląd Dermatologiczny, 2011)
Introduction . T-cell lymphoma dominates among primary cutaneous lymphomas. The most common entity is mycosis fungoides. The first cutaneous changes are often unspecific and cause many diagnostic problems. Objective . Retrospective analysis of patients with primary cutaneous lymphomas hospitalized in the Dermatology and Venerology Department of MU in Lodz in 1985-2005. Material and methods . The study was based on an analysis of case records of 64 patients (43 males and 21 females) of average age 60 years and was focused on preliminary diagnosis, medical history, clinical examination (characteristics and location of cutaneous changes), laboratory investigation and histological examination of a cutaneous specimen. Results . The analysed group comprised 60 cases of mycosis fungoides and 4 of Sezary syndrome. In 70% of patients with the final diagnosis of mycosis fungoides, the preliminary diagnosis included other diseases (among them eczema and psoriasis). The most common complaint was pruritus. Cutaneous changes were disseminated, mainly located on upper and lower extremities. Conclusions . In most cases of primary cutaneous lymphomas the early skin symptoms of the disease were non-specific and caused diagnostic problems.